The Exploration of English Consonant: A Literature Review - Aisyah Rizqa Fitri Siregar; Yani Lubis; Siti Julaika (Pusat Riset dan Inovasi Nasional, 2023)
This research focuses on the study of English consonants. This research used literature review method to explore the English consonant such as the manner of articulation, the organs produced the consonant, and the benefit of learning English consonant. The results are, the first section explores the specific anatomical structures and organs within the vocal tract that play a role in producing consonant sounds. The second section examines the different ways in which airflow is obstructed or modified during consonant production, highlighting categories such as plosives, fricatives, affricates, nasals, and approximants. The third section investigates the various factors that influence consonant pronunciation, including phonetic, phonological, sociolinguistic, and individual factors, as well as the impact of language contact and second language acquisition. The final section discusses the advantages of learning English consonants, such as improved communication skills, enhanced listening comprehension, expanded vocabulary acquisition, and increased oral fluency. Overall, this research provides valuable insights into the study of English consonants, offering a comprehensive understanding of their production, variations, and implications for language instruction and speech pathology.